Numerical Modeling of GaAs Solar Cell Performances - Abderrezek, M.; Djahli, F.; Fathi, M.; Ayad, M. (Elektronika ir Elektrotechnika, 2013)
The process of modeling photovoltaic devices is a tedious task in that it depends heavily on several intrinsic and extrinsic properties of the material. In this paper, numerical solutions are obtained using the Personal Computer 1 Dimension (PC1D) software package in order to improve solar cells performance. The analysis deals with high efficiency GaAs solar cells, in order to search the technological parameters leading to optimal performances of the cells, the effects of the doping level and the thicknesses of the base and emitter layers were also investigated. The optimal fill factor and the conversion efficiency that were obtained are 86.76 % and 25.8 % respectively. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5392